Tune up to literacy original songs and activities for kids - Balkin, Alfred (IG library, 2009)
Encourage literacy with twenty original songs by musician and educator Al Balkin! Children's and school librarians will welcome Tune Up to Literacy, a handy package of music and activities that musically introduces and reinforces crucial literacy concepts such as the alphabet, vowels, consonants, nouns, verbs, adjectives, sentence construction, punctuation, sequence, rhyming, and much, much more. The book includes: 20 original songs to encourage children's development of literacy; rhyme-a-ton rhyming dictionary of commonly used one-syllable words; activities related to each song-- from inventing new verses to telling stories to playing flash-card games. Catchy and strikingly original, the road-tested songs of Tune Up to Literacy are proven tools for acquainting kids with basic literacy concepts.